PERAN PERKEMBANGAN MORAL TERHADAP PERILAKU PROSOSIAL REMAJA - Fredericksen Victoranto Amseke; Marleny Purnamasary Panis (Psyche: Jurnal Psikologi, 2020)
ABSTRACTThe purpose of this study was to determine the effect of moral development on prosocial behavior in students grade VIII in SMP Negeri"X" at Kota Kupang. This is a quantitative research.  The research’s population was all students grade VIII in SMP Negeri "X" at Kota Kupang with the total amount of 352 students. A sample of 78 students was taken by cluster random sampling technique. Instruments data collection were the scale of moral development and the scale of prosocial behavior. The data analysis technique was simple linear regression.Correlation analysis results show significant positive correlation between moral development and prosocial behavior with R = 0.568.. Simple linear regression analysis was performed to predict prosocial behavior based on moral development (F=36,188, p = 0.000 (<0.05) with coefficient determination R2 = 0.323, which means that the influence of moral development on prosocial behavior in students grade VIII in SMP Negeri "X" at Kota Kupang is 32.3%. This study shows the level of moral development in students grade VIII in SMP Negeri "X" at Kota Kupang is categorized as high at the level of 43.7% while at the same time the level of prosocial behavior is also in the high category at the level of 39.7%. The increased level of moral development relates to the higher level of prosocial behavior in adolescents. Keywords: Moral Development, Prosocial Behavior ABSTRAKTujuan penelitian ini untuk mengetahui pengaruh perkembangan moral terhadap perilaku prososial pada siswa kelas VIII di SMP Negeri “X” Kota Kupang. Penelitian ini adalah penelitian kuantitatif. Populasi penelitian adalah seluruh siswa kelas VIII di SMP Negeri “X” Kota Kupang berjumlah 352 siswa. Sampel berjumlah 78 siswa diambil dengan teknik cluster random sampling. Instrumen pengumpulan data adalah skala perkembangan moral dan skala perilaku prososial. Teknik analisis data adalah regresi linear sederhana. Hasil analisis korelasi menunjukkan korelasi positif yang signifikan antara perkembangan moral dan perilaku prososial dengan nilai R = 0,568. Analisis regresi linear sederhana dilakukan untuk memprediksi perilaku prososial berdasarkan perkembangan moral (F = 36,188,  p = 0,000 (< 0,05)  dengan nilai koefisien determinasi R2= 0,323. Artinya pengaruh perkembangan moral terhadap perilaku prososial siswa kelas VIII di SMP Negeri “X” Kota Kupang sebesar 32,3%. Penelitian ini menunjukkan tingkat perkembangan moral siswa kelas VIII di SMP Negeri "X" di Kota Kupang dikategorikan tinggi pada level 43,7%, sementara itu pada saat yang sama tingkat perilaku prososial juga berada pada kategori tinggi pada level 39,7%. Semakin tinggi perkembangan moral semakin meningkat pula perilaku prososial remaja.   Kata Kunci:  Perkembangan Moral, Perilaku Prososial.